PERKEMBANGAN PROFESIONAL GURU DAN REFORMASI KEPENDIDIKAN - Zulyadaini Zulyadaini (Universitas Batanghari Jambi, 2012)
The teacher is an array of values, wisdom, knowledge and skills from the previous generation to a generation later. A teacher who has a high professionalism are required to have adequate competence in carrying out its work. In accordance with Act No. 2 of 2005 on teachers and professors, that teachers should have the competence, namely: 1)Competence pedagogik, the ability of the hussy mastery learning materials widely and in depth which include;(a) the concept, structure and methods of science/technology/art teaching material with coherent; (b) the material taught in the school curriculum; (c) the relationship between the concepts of related subjects; (d) application of scientific concepts in everyday life; and (e) competition in a professional manner in the global context while preserving values and national culture.2)personality competence is the ability of personality include; steady, stable, mature, wise and thoughtful, authoritative, noble character, became an example for the students and the community, evaluate its own performance and develop themselves continuously. 3)Professional Competence, which is the ability of the mastery learning materials widely and in depth which include;(a) the concept, structure, and method of science/technology/art overshadowing/coherent with learning materials; (b) the material taught in the school curriculum; (c) the relationship between the concepts of related subjects; (d) application of scientific concepts in everyday life; and (e) competition in a professional manner in the global context while preserving national culture and values.4)Social Competence that is the ability of educators as part of the community to: (a) communicating and interpreting; (b) the use of information and communication technology functionally; (c) mix effectively with fellow learners, educators, classrooms, parent/guardian learners; and (d) hanging out in manners with the surrounding communities.Keyword : Teacher, Competence, Professional